The mother in 4 Maccabees - an example of rational choice in religion - Fuhrmann, S. (Journal for semitics, 2008)
The focus of this paper falls on the mother as the personification of a pious acting according to the λογισμός. This concept, one of the core ideas of 4 Maccabees, must be understood in terms of economic calculating, therefore indicating that pious reason implies a kind of cost-benefit analysis. The mother in the said text now functions as a paradigm of such analysis, offering her sons and her life (costs) to receive them back from God in eternity (benefits).